PENERAPAN TERAPI RELAKSASI ZIKIR TERHADAP STRES PADA KLIEN DENGAN HIPERTENSI ESENSIAL DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: APPLICATION OF ZIKIR RELAXATION THERAPYON STRESS IN CLIENTS WITH ESSENTIAL HYPERTENSION IN THE REGION OF PUSKESMAS ROWOSARI SEMARANG - Merid Lechan; Margiyati Margiyati (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
Hypertension is an increase in blood pressure above 140/90 mmHg. One of the causes of hypertension that is difficult to control is stress which can worsen the client's condition so that it is needed to handle through stress management. Zikir relaxation therapy is one of the relaxation therapies with an elemental approach to spirituality that is useful for reducing stress. The purpose of this case study is to illustrate the application of Zikir Relaxation Therapy to stress on clients with essential hypertension in the area assisted by the Rowosari Health Center Semarang. This type of research is descriptive using the case study approach method. The subjects used were two respondents with the criteria of clients with essential hypertension, level I-II hypertension, and moderate stress levels. The form of intervention is the application of Zikir relaxation therapy 4 times in 2 weeks (twice a week). The analysis is used to determine the stress level using the DSS (Distress Symptom Scale) measuring instrument. The results showed a decrease in stress levels before and after the administration of Zikir therapy from moderate stress to mild stress for subject I with a decrease of 36 scores and from moderate stress to normal for subject II with a decrease in 40 scores. The average reduction in stress levels of the two subjects after Zikir relaxation from an average score of 63 to 38. From the results of these studies, the provision of zikir therapy can be used as an intervention to reduce stress levels in clients with essential hypertension.